Outcome of Penetrating Keratoplasty from a Corneal Unit in Pakistan - Kamal, Mazhar-ul-Hassan, Partab Rai, Muhammad Nasir Bhatti, Yawar Zaman, P.S. Mahar, Azizur Rahman, Muhammad Fazal (Pakistan Journal of Ophthalmology, 2009)
Purpose: To evaluate the outcome of penetrating keratoplasty (PKP) at a corneal unit in Pakistan. Material and Methods: Penetrating keratoplasty (PKP) alone or triple procedure (PKP combined with extracapsular cataract extraction and intraocular lens implantation) was performed in 30 eyes of 30 patients at Al-Ibrahim Eye Hospital/Isra Postgraduate Institute of Ophthalmology, Karachi from January 2003 to December 2007. The outcome was evaluated in terms of graft survival (number of clear grafts at final follow-up) and final best-corrected visual acuity. Results: Out of 30 patients underwent PKP. 73.3% were male and 26.7% female. Mean recipient age was 38.1 years (range 14-82). Leading indication of PKP was corneal scar (46.7%). PKP alone was performed in 70% patients and 30% patients had triple procedure. Mean follow-up period after surgery was 12.3 months (range1-36). Overall graft survival was 61%. Excluding failed grafts, final best-corrected visual acuity achieved was: 20/40 or better in 33.3% patients, 20/50 - 20/150 in 41.7% patients and 20/200 or worse in 25% patients. Keratoconus had most favorable outcome with graft survival of 88.9% and final visual acuity of 20/40 or better in 55.6% patients. Graft survival and final bestcorrected visual acuity of 20/40 or better in remaining indications were, corneal scar (78.6% & 14.3%), pseudophakic bullous keratopathy (75% & 25%), and other indications (66.7% & 0.0%). Conclusion: This series showed that PKP is an effective procedure for corneal disease with poor vision. Visual outcome was good especially in cases of keratoconus.